A Comparison of Imaging Techniques to Monitor Tumor Growth and Cancer Progression in Living Animals. (10th November 2011) - Puaux, Anne-Laure; Ong, Lai Chun; Jin, Yi; Teh, Irvin; Hong, Michelle; Chow, Pierce K. H.; Golay, Xavier; Abastado, Jean-Pierre
Abstract : Introduction and Purpose . Monitoring solid tumor growth and metastasis in small animals is important for cancer research. Noninvasive techniques make longitudinal studies possible, require fewer animals, and have greater statistical power. Such techniques include FDG positron emission tomography (FDG-PET), magnetic resonance imaging (MRI), and optical imaging, comprising bioluminescence imaging (BLI) and fluorescence imaging (FLI). This study compared the performance and usability of these methods in the context of mouse tumor studies. Methods . B16 tumor-bearing mice (n = 4 for each study) were used to compare practicality, performance for small tumor detection and tumor burden measurement. Using RETAAD mice, which develop spontaneous melanomas, we examined the performance of MRI (n = 6 mice) and FDG-PET (n = 10 mice) for tumor identification. Results . Overall, BLI and FLI were the most practical techniques tested. Both BLI and FDG-PET identified small nonpalpable tumors, whereas MRI and FLI only detected macroscopic, clinically evident tumors. FDG-PET and MRI performed well in the identification of tumors in terms of specificity, sensitivity, and positive predictive value. Conclusion . Each of the four methods has different strengths that must be understood before selecting them for use.